Effects of trona (sodium sesquicarbonate) on physio-biochemical profiles and cardiovascular risk indices in Wistar rats - Emeka Ugwuanyi; Obinna Onyejekwe; Moniloye Akanfe (The Iranian Journal of Veterinary Science and Technology)
Purpose of the study: This investigation aimed to assess the impact of trona on the cardiovascular risk markers and physio-biochemical profiles of rats administered graded dosages over 28 days. Five groups (n = 5) of rats—A, B, C, D, and E—were randomly assigned, with E acting as the control. For 28 days, rats in groups A, B, C, and D were administered trona at doses of 50, 100, 200, and 400 mg/kg, correspondingly. All over the investigation, distilled water was provided to the animals in the control group. We measured body weights, oxidative stress, hematology, hepatorenal profiles, somatic organs, fasting blood glucose (FBG) levels, and cardiovascular risk indices (CVRI). Findings: Rats administered 400 mg/kg had higher FBG levels (p < 0.05) than the control group. Group D showed decreases (p < 0.05) in erythrocytic indices, total protein level, and heart-body index with concurrent increases (p < 0.05) in total leucocyte counts (TLC) and creatinine levels in comparison to the control group. Rats in groups B, C, and D showed higher levels of catalase activity (p < 0.05) compared to the control group. Rats given 100 mg/kg or above of trona showed increases (p < 0.05) in CVRI compared to controls. Conclusions: There were dose-dependent harmful effects on the erythrocytic indices, high exposure to T2DM (type-2 diabetes mellitus), and increased CVRI levels in rats dosed orally with ≥100 mg/kg trona for 28 days.